The means of professional training for using pedagogical technologies - Бєляєв, Сергій Борисович (Scientific notes of the pedagogical department, 2015)
On the modern stage of national educational system development, quality professional training of a future teacher stipulates mastering innovative pedagogical technologies. The article is focuses on the need for independent educational activity, on the basis of requirements set for teacher vocational training and methodological approaches important.